Determinants of Consumer Purchase Decisions: The Roles of Service Quality, Location, and Café Atmosphere at Hidden Kinou - Ni Made Ayu Dwi Putri; Anak Agung Putu Agung; Ni Made Satya Utami (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
The era of increasingly fierce competition, driven by the large number of competitors in the vicinity of the café, requires café owners to pay attention to various factors that can influence consumers’ purchasing decisions. This study aims to investigate the impact of service quality, location, and café atmosphere on purchasing decisions. A quantitative method was employed in this study. The selected population consists of consumers who have made more than one purchase at Hidden Kinou and are at least 17 years old, with a sample size of 100 people. Data analysis techniques included validity testing, reliability testing, multiple linear regression analysis, classical assumption testing, F-tests, the coefficient of determination, and t-tests. The study findings indicate that service quality, location, and café atmosphere have a positive and significant impact on purchasing decisions.